2010
DOI: 10.1189/jlb.0710413
|View full text |Cite
|
Sign up to set email alerts
|

NKG2A inhibits NKG2C effector functions of γδ T cells: implications in health and disease

Abstract: The CD94/NKG2 complex is expressed on T and NK lymphocytes. CD94 molecules covalently associate to activating or inhibitory NKG2 molecules, and their expression finely tunes cell responses. Human γδ T cells express several NKRs. Expression of these receptors is confined to the cytolytic Vδ2 subset, which coexpresses the FcγRIII CD16 and CD45RA and has been defined as Vγ9Vδ2 T(EMRA) cells. We show that the CD94/NKG2C complex, associated with KARAP/DAP12, is fully functional in γδ T cells, as determined by measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 56 publications
6
30
0
Order By: Relevance
“…Similar to a previous study [20], the fraction of NKG2C + γδ + T cells varied widely in all groups of this study. However, a slight increase of activating NKG2C + γδ + T cells among the PB lymphocytes was observed in the BD group compared to the HC (0.5 vs. 0.3%, P = 0.008).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Similar to a previous study [20], the fraction of NKG2C + γδ + T cells varied widely in all groups of this study. However, a slight increase of activating NKG2C + γδ + T cells among the PB lymphocytes was observed in the BD group compared to the HC (0.5 vs. 0.3%, P = 0.008).…”
Section: Resultssupporting
confidence: 86%
“…CD94/NKG2C complex is functional with IFN-γ production, T cell proliferation and cytolytic activity, whereas NKG2A expression was found on all γδ T cell memory subsets, suggesting a crucial role of the inhibitory signal provided by this receptor on γδ T cell responses [20]. In BD and in A-BD a slight increase of activating NKG2C + γδ T cells has been detected showing an activation status of the cells, although the other activating receptor, NKG2D, was decreased in BD.…”
Section: Discussionmentioning
confidence: 99%
“…As reviewed, NKG2A, an inhibitory receptor expressed by NK cells and CD8 + T cells, plays an important role in HIV, HCV [38], [39], and HBV [40] infections. NKG2A also mediates suppressive signaling in human γδ T cells [16], [41]. In the current study, we found that most γδ DNT cells expressed NKG2A, and the frequency of HLA-E in CD8 + αβ T cells was higher in patients with CHB.…”
Section: Discussionsupporting
confidence: 56%
“…The cytolytic function of γδ T cells is tightly regulated by receptors such as NKG2A, NKG2D and NKG2C (50, 51). HIV/SIV infection activates γδ T cells as shown here by the increase in CD69 + γδ T cells (Fig.…”
Section: Discussionmentioning
confidence: 99%